British Association for Sexual Health and HIV: framework for guideline development and assessment. (March 2016) - Kingston, Margaret; Radcliffe, Keith; Cousins, Darren; Fifer, Helen; FitzGerald, Mark; Grover, Deepa; Hardman, Sarah; Higgins, Stephen; Rayment, Michael; Sullivan, Ann
Summary: The Clinical Effectiveness Group of the British Association for Sexual Health has updated their methodology for the production of national guidelines for the management of sexually transmitted infections and related conditions. The main changes are the adoption of the GRADE system for assessing evidence and making recommendations and the introduction of a specific Conflict of Interests policy for Clinical Effectiveness Group members and guideline authors. This new methodology has been piloted during the production of the 2015 British Association for Sexual Health & HIV guideline on the management of syphilis.